PENGEMBANGAN MATA PELAJARAN BERBASIS E-LEARNING DI SEKOLAH MENENGAH KEJURUAN - Adikara, Fransiskus (Universitas Esa Unggul, 2017)
AbstractCommunity Service at Secondary School in Tanjung Duren Barat III No. 1 Jakarat, precisely Yayasan Pendidikan Al Chasanah aims to share knowledge or transfer knowledge about the implementation of computer-based information system as a support of education services to Teachers and Education Staff to understand and be able to develop learning according to their needs. Specific targets to be achieved are the understanding and ability to implement computer-based information system as a supporter of education services at Yayasan Pendidikan Al Chasanah in order to be able to adjust from the demands and needs of the business world and industry, as supporter and source of extension libraries are also given on the development of subjects based e-learning. The methods used in the form of counseling with practical delivery through the transfer of science and the presentation of e-learning based e-learning development steps that really can be accepted and add to the essence of knowledge and skills of Teachers and Education Staff. Granting the material in the form of an understanding of e-learning and examples of materials that can be used for e-learning has increased the insight of the teachers to be able to develop teaching materials. From the results of this counseling the Principal invites all teachers to be able to take advantage of this new knowledge and insight to be able to meet the expectations of Yayaysan run e-learning program for students in the academic year 2018/2019. It can be concluded that this extension activity is in line with the Principals work plan and the Al Chasanah Education Foundation in addition to being useful for the teachers involved. Keywords: e-learning, educational institution, community service AbstrakPelaksanaan Pengabdian Kepada Masyarakat di Sekolah Menengah di wilayah Tanjung Duren Barat III No. 1 Jakarat, tepatnya Yayasan Pendidikan Al Chasanah bertujuan untuk berbagi pengetahuan atau transfer knowledge mengenai penerapan sistem informasi berbasis komputer sebagai pendukung pelayanan pendidikan kepada Guru dan Staf Pendidikan agar memahami dan berkemampuan untuk pengembangan pembelajaran sesuai kebutuhannya. Target khusus yang ingin dicapai adalah pemahaman dan kemampuan untuk menerapkan sistem informasi berbasis komputer sebagai pendukung pelayanan pendidikan di Yayasan Pendidikan Al Chasanah agar mampu menyesuaikan dari tuntutan dan kebutuhan dunia usaha dan dunia industri, sebagai pendukung dan sumber pustaka penyuluhan diberikan juga pada sisi pengembangan mata pelajaran berbasis e-learning. Adapun metode yang digunakan berbentuk penyuluhan dengan penyampaian yang praktis melalui transfer ilmu dan sajian langkah-langkah pengembangan mata pelajaran berbasis e- learning sehingga benar-benar dapat diterima dan menambah esensi pengetahuan dan keterampilan Guru dan Staf Pendidikan. Pemberian materi berupa pemahaman mengenai e-learning dan contoh-contoh dari materi yang bisa digunakan untuk e-learning telah menambah wawasan para Guru untuk dapat mengembangkan bahan pengajarannya. Dari hasil penyuluhan ini Kepala Sekolah mengajak seluruh Guru untuk dapat memanfaatkan pengetahuan dan wawasan barunya ini untuk dapat memenuhi harapan Yayaysan menjalankan program e-learning bagi anak didiknya di tahun ajaran 2017/2018. Dapat disimpulkan bahwa kegiatan penyuluhan ini sejalan dengan rencana kerja Kepala Sekolah dan Yayasan Pendidikan Al Chasanah selain berguna bagi para guru-guru yang terlibat. Kata kunci: e-learning, lembaga pendidikan, pengabdian masyarakat